Allergic disease trajectories up to adolescence: Characteristics, early‐life, and genetic determinants. Issue 3 (19th September 2022) - Kilanowski, Anna; Thiering, Elisabeth; Wang, Gang; Kumar, Ashish; Kress, Sara; Flexeder, Claudia; Bauer, Carl‐Peter; Berdel, Dietrich; von Berg, Andrea; Bergström, Anna; Gappa, Monika; Heinrich, Joachim; et al.
Abstract: Background: Allergic diseases often develop jointly during early childhood but differ in timing of onset, remission, and progression. Their disease course over time is often difficult to predict and determinants are not well understood. Objectives: We aimed to identify trajectories of allergic diseases up to adolescence and to investigate their association with early‐life and genetic determinants and clinical characteristics. Methods: Longitudinal k‐means clustering was used to derive trajectories of allergic diseases (asthma, atopic dermatitis, and rhinitis) in two German birth cohorts (GINIplus/LISA). Associations with early‐life determinants, polygenic risk scores, food and aeroallergen sensitization, and lung function were estimated by multinomial models. The results were replicated in the independent Swedish BAMSE cohort. Results: Seven allergic disease trajectories were identified: "Intermittently allergic, " "rhinitis, " "early‐resolving dermatitis, " "mid‐persisting dermatitis, " "multimorbid, " "persisting dermatitis plus rhinitis, " and "early‐transient asthma." Family history of allergies was more prevalent in all allergic disease trajectories compared the non‐allergic controls with stronger effect sizes for clusters comprising more than one allergic disease (e.g., RRR = 5.0, 95% CI = [3.1–8.0] in the multimorbid versus 1.8 [1.4–2.4] in the mild intermittently allergic cluster). Specific polygenic risk scores for single allergic diseases were significantly associated with their relevant trajectories. The derived trajectories and their association with genetic effects and clinical characteristics showed similar results in BAMSE. Conclusion: Seven robust allergic clusters were identified and showed associations with early life and genetic factors as well as clinical characteristics. Abstract : We identified seven allergic disease trajectories up to adolescence, which are corresponding to clinical observation in the German GINIplus and LISA studies and replicated the results in the Swedish BAMSE cohort. The clusters can be characterized using polygenic risk scores and early‐life determinants, which support the hygiene hypothesis. The clusters also pose clinical implications for allergic sensitization, increasing with number of present allergic diseases, and lung function.Abbreviations: BAMSE, Barn/Child Allergy Milieu Stockholm Epidemiology; GINIplus, German Infant Study on the Influence of Nutrition Intervention plus Air pollution and Genetics on Allergy Development; LISA, Influence of Life‐style factors on Development of the Immune System and Allergies in East and West Germany study; PRS, polygenic risk score.